Effects of radial growth rate on wood properties and lumber qualities in plantation-grown Picea koyamae - Futoshi Ishiguri; Ikumi Nezu; Yusuke Takahashi; Sarkhad Murzabyek; Kana Yamashita; Toshio Katsuki; Kouhei Otsuka; Jyunichi Ohshima; Shinso Yokota (Journal of Wood Science)
Abstract Picea koyamae Shiras., which grows naturally in Japan, is listed as an endangered species. Establishing plantations is one solution for conserving this species and preventing its extinction. To promote the establishment of plantations to conserve this species through wood utilization, it is essential to clarify the relationship between properties and radial growth rate. We evaluated the wood properties and lumber qualities of 51-year-old P. koyamae plantation trees with different radial growth rates (dominant, co-dominant, and suppressed trees) using mixed-effects models, although the number of sample trees was limited. The variance components showed larger values in the growth category for stress-wave velocity and basic density, but the random-effect parameter estimates for these two properties were small in dominant and co-dominant trees. Similar results of mixed-effects modeling were also obtained in the air-dry density and mechanical properties of lumber. Model selection for radial variations of wood properties indicated that the radial growth rate did not influence radial variations of wood properties. The wood properties and lumber qualities of dominant trees were the same as those of co-dominant trees, indicating that lumber from dominant trees from plantations of P. koyamae did not always have lower lumber qualities.